2018
DOI: 10.1111/hir.12231
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating digital libraries: a systematised review

Abstract: Because there are fewer studies of digital libraries evaluation in the health sector, the specific features of health digital libraries should be addressed by librarians and health digital library designers to develop specific models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…Table 1 shows that out of 95 selected studies, 28 studies (29.47%) have applied the SERVQUAL model, followed by 20 studies (21.05%) reported application of LibQUAL model, 8 studies (8.42%) applied the Structural Equation Modelling, 7 studies (7.36%) measured the service quality by applying two service quality models Cabrerizo et al (2017), Chen (2016), Li and Yang (2013) and Xi et al (2018) 4 studies (4.21%) applied a self proposed model (Barhoumi, 2016; Borbely, 2011; Powelson and Reaume, 2012; Mehrjerdi, 2017) and 2 studies reported the application of a fuzzy based model (Tooranloo et al, 2018; Lee et al, 2011). Twenty-five studies (26.31%) had no mention of any models Corrall (2017), Brettle et al (2011), Cabrerizo et al (2012), Einasto (2014), Gupta and Singh (2012), Helman and Horowitz (2001), Heradio et al (2012), Hernon and Nitecki (2001), Kim (2011), Partap (n.d), Rahimi et al (2018), Stokić et al (2019).…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows that out of 95 selected studies, 28 studies (29.47%) have applied the SERVQUAL model, followed by 20 studies (21.05%) reported application of LibQUAL model, 8 studies (8.42%) applied the Structural Equation Modelling, 7 studies (7.36%) measured the service quality by applying two service quality models Cabrerizo et al (2017), Chen (2016), Li and Yang (2013) and Xi et al (2018) 4 studies (4.21%) applied a self proposed model (Barhoumi, 2016; Borbely, 2011; Powelson and Reaume, 2012; Mehrjerdi, 2017) and 2 studies reported the application of a fuzzy based model (Tooranloo et al, 2018; Lee et al, 2011). Twenty-five studies (26.31%) had no mention of any models Corrall (2017), Brettle et al (2011), Cabrerizo et al (2012), Einasto (2014), Gupta and Singh (2012), Helman and Horowitz (2001), Heradio et al (2012), Hernon and Nitecki (2001), Kim (2011), Partap (n.d), Rahimi et al (2018), Stokić et al (2019).…”
Section: Resultsmentioning
confidence: 99%
“…To identify and analyse the challenges associated with FRBR implementation. Gaona-Garcia et al (2017), Ndungu (2017), Kiryakos & Sugimoto (2018), Rahimi et al (2018), Koh & Muthupalaniappen (2018), Beene et al (2020), Alvite-Diez (2021), Zavalin & Miksa (2021).…”
Section: Research Objectivesmentioning
confidence: 99%
“…The limitation of Alokluk and Al-Amri's research was it had not shown an evaluation component that was able to evaluate the socialization procedure of digital libraries. Rahimi et al's research [41] showed the use of the DigiQUAL model in evaluating the quality of digital library services. The limitation of Rahimi et al's research was it had not shown an evaluation component that was able to measure the socialization form of the existence of a digital library.…”
Section: Contentmentioning
confidence: 99%